The effectiveness of using Metallocene fertilizers for the spray-dressing of winter wheat - Vafin Ilshat (EDP Sciences, 2021)
This article presents the impact assessment results for the spay-dressing of different Metallocene compound fertilizers containing chelated microelements on the yield and quality of winter wheat seeds of the Kazanskaya 560 variety. The research was carried out on the grey forest soils in the Kama region of the Republic of Tatarstan in 2017–2020. The plants were dressed with fertilizers in the autumn and the spring and summer period. In the autumn, we used the fertilizer containing manganese (Metallocene D), and in the spring and summer period (the tillering and earing stages of the winter wheat), we used the Metallocene Universal compound fertilizer with several microelements. During the research, we established that applying the manganese-containing Metallocene D in the autumn has a significant positive effect on the growth and dry biomass accumulation of the winter wheat. The dressing with Metallocene Universal during the tillering and earing stages following the application of Metallocene D in the autumn resulted in an increased/stimulated plant growth and development. The highest yield of winter wheat (3.45 t/ha or 46 % above the reference value) was obtained through the dressing of Metallocene D at a rate of 2 l/ha in the autumn, and the spraying of the plants with Metallocene Universal done twice during the spring and summer period. The autumn application of Metallocene D and the twofold application of Metallocene Universal improve the qualitative parameters of new winter wheat seeds. The use of fertilizers in questions improved the laboratory germination of the seeds and significantly reduced the root rot agent infection rate. The twofold dressing during the spring and summer period following the autumn dressing helped to suppress the most dangerous infections, such as the fusarium blight and the Helmintosporium disease, in the new seeds almost completely. The research conducted showed that Metallocene fertilizers can be successfully used to improve the production of winter wheat and seeds.